Broken faith : inside the Word of Faith Fellowship, one of America's most dangerous cults - Weiss, Mitch; Mohr, Holbrook (Hanover Square Press, 2020)
In 1979, a fiery preacher named Jane Whaley attracted a small group of followers with a promise that she could turn their lives around. In the years since, Whaley<U+2019>s following has expanded to include thousands of congregants across three continents. In their eyes she<U+2019>s a prophet. And to disobey her means eternal damnation. The control Whaley exerts is absolute: she decides what her followers study, where they work, whom they can marry- even when they can have sex. Based on hundreds of interviews, secretly recorded conversations, and thousands of pages of documents, Pulitzer Prize winner Mitch Weiss and Holbrook Mohr<U+2019>s Broken Faith is a terrifying portrait of life inside the Word of Faith Fellowship, and the harrowing account of one family who escaped after two decades.